Fast Range Decoupling Algorithm for Metamaterial Aperture Real-time Imaging - Gao, Yuteng; Peng, Wencan; Wang, Min; Guo, Chenjiang; Ding, Jun (Applied Computational Electromagnetics Society Journal (ACES), 2021)
While metamaterial aperture imaging systems do not require mechanical scanning equipment or complex components by employing a spatially variant radiation field, they require large amount of data and many computations. In this paper, we deduce the contribution of the resonator to the radiation fields of the metamaterial aperture. We propose a fast range decoupling algorithm that can improve the data processing speed and obtain real-time images of far-field scenes. The algorithm decomposes the scene into numerous range cells, drastically reduces the range of interest, and reconstructs the scene in parallel. Simulation results show that computational cost is significantly decreased and image quality is maintained.